Conflicting spatial representations impairs object tracking performance in an aerospace environment. Issue 167 (November 2022) - Geeseman, Joseph W.; Balters, Stephanie
Abstract: The purpose of this study is to extend the small number of applied research studies in Unmanned Aerial Systems (UAS) sensor control to a more ecologically valid human performance application set (i.e., airborne object tracking). In this study, United States Naval Aviators and Aircrew ( N = 8) assumed the role of a sensor operator for a simulated unmanned aerial system while riding in an airborne Lockheed P-3 Orion aircraft. The P-3 flew in two flight conditions that differed in the level of intermittent ascending, descending, and turning profiles to induce two levels of spatial incongruity with the UAS sensor operator screen. Participants also performed trials on the ground to establish baseline performance measures. Results show that the incongruent visual and vestibular cues experienced by the participants during flight induced spatial incongruity and an overall decrease in operator tracking performance [F(2, 3872) = 14.04, p < 0.001)] compared to ground baseline trials. Exploratory findings suggest that motion sickness could be an important consideration for future in-flight UAS sensor control. Interestingly, results also indicate that performance decrements due to the flight environment alleviate to normal performance levels over time. Therefore, a training regime may suffice to ameliorate the effects of spatially discordant environments on human performance. Highlights: This study is the first of its kind to systematically evaluate the impact of spatial discordance on human performance while in flight. Results show that the disparate visual and vestibular cues experienced by the participants significantly induced spatial discordance and an overall decrease in tracking performance ( t = 18.83, p = .001) compared to trials during straight and level flight and ground baseline trials. Results also indicate that performance decrements due to the flight environment alleviate to normal performance levels over time. Therefore, a training regime may suffice to ameliorate the effects of spatially discordant environments on human performance.